2005
DOI: 10.1063/1.1894615
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale effects on ion conductance of layer-by-layer structures of gadolinia-doped ceria and zirconia

Abstract: Layer-by-layer structures of gadolinia-doped ceria and zirconia have been synthesized on Al2O3(0001) using oxygen plasma-assisted molecular beam epitaxy. Oxygen ion conductivity greatly increased with an increasing number of layers compared to bulk polycrystalline yttria-stabilized zirconia and gadolinia-doped ceria electrolytes. The conductivity enhancement in this layered electrolyte is interesting, yet the exact cause for the enhancement remains unknown. For example, the space charge effects that are respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 9 publications
5
129
0
Order By: Relevance
“…The conductivities of the composite materials consisting of the doped ceria and lanthanum silicate could be enhanced obviously by a nanocomposite process [2]. The oxygen ionic conductivity of nano-structured layer-by-layer electrolytes composed of gadolinia-doped ceria and zirconia could be increased greatly [4]. In YSZ-SrTiO 3 epitaxial heterostructures, a high lateral oxygen ionic conductivity, showing up to eight orders of magnitude enhancement near room temperature, was reported [6].…”
Section: mentioning
confidence: 79%
See 1 more Smart Citation
“…The conductivities of the composite materials consisting of the doped ceria and lanthanum silicate could be enhanced obviously by a nanocomposite process [2]. The oxygen ionic conductivity of nano-structured layer-by-layer electrolytes composed of gadolinia-doped ceria and zirconia could be increased greatly [4]. In YSZ-SrTiO 3 epitaxial heterostructures, a high lateral oxygen ionic conductivity, showing up to eight orders of magnitude enhancement near room temperature, was reported [6].…”
Section: mentioning
confidence: 79%
“…The former is a complex work for that it is not easy to find a new suitable compound. The composite process and nano-technology were reported to be the effective ways to improve dramatically the oxygen-ionic conductivity [2][3][4][5][6][7][8][9]. The conductivities of the composite materials consisting of the doped ceria and lanthanum silicate could be enhanced obviously by a nanocomposite process [2].…”
Section: mentioning
confidence: 99%
“…In fact, it has been reported that thin films made of alternated multilayers (at least about 30 u.c. each) of GDC and Zirconia showed a small enhancement in conductivity with respect to the parent materials [7]. This increase has been attributed to a combination of lattice strain and extended defects due to lattice mismatch between the heterogeneous structures.…”
Section: Introductionmentioning
confidence: 93%
“…In general, literature data are quite consistent concerning the increased oxygen-ion conductivity of interfaces showing a large dislocation density, 4,7,9 but whether the interfacial strain can play a significant role in enhancing the ionic conductivity is still quite a controversial issue.…”
mentioning
confidence: 93%